Urban vegetation change after a hundred years in a tropical city (San José de Costa Rica) - Monge Nájera, Julián (2010)
Urban vegetation is of key importance because a large proportion of the human population lives in cities. Nevertheless, urban vegetation is understudied outside central Europe and particularly, little is known about the flora of tropical Asian, African and Latin American cities. We present an estimate of how the vegetation has changed in the city of San José, Costa Rica, after about one century, with the repeat photography technique (based on a collection of 19th and early 20th century photographs by José Fidel Tristán and others) and with data from the Costa Rican National Herbarium. We found little vegetation change in the landscape of San José during the 20th century, where a total of 95 families and 458 species were collected in the late 19th and early 20th century. The families with most species were Asteraceae, Fabaceae, Poaceae, Lamiaceae, Euphorbiaceae, Solanaceae, Cyperaceae, Acanthaceae, Malvaceae, Piperaceae and Verbenaceae. Similar results have been found in Europe, where the number of plant species often is stable for long periods even when the individual species vary.